Matematyka
stonee
2017-06-23 23:16:57
Rozwiąż równania: a) (x+5)^2 -(x-3)^2 = x+1 b) (x+1)^2 - (x-3)(x+3)-2 = 2(x-1)^2 c) (x+3)^2 - (4-x)(4+x) = 2(x-1)^2 +1 DAJE NAJ!!!
Odpowiedź
JUNIR
2017-06-24 04:58:22

Użyte wzory skróconego mnożenia: (a+b)²=a²+2ab+b² (a-b)²=a²-2ab+b² (a-b)(a+b)=a²-b² a) (x+5)²-(x-3)²=x+1 x²+2·5·x+5²-(x²-2·3·x+3²)=x+1 x²+10x+25-x²+6x-9=x+1 16x+16=x+1 16x-x=1-16 15x=-15 x=-1 b) (x+1)²-(x-3)(x+3)-2=2(x-1)² x²+2·1·x+1²-(x²-3²)-2=2(x²-2·1·x+1²) x²+2x+1-x²+9-2=2(x²-2x+1) 2x+8=2(x²-2x+1) x+4=x²-2x+1 x²-3x-3=0 a=1 b=-3 c=-3 [latex]Delta=b^2-4ac=(-3)^2-4cdot1cdot(-3)=9+12=21\sqrtDelta=sqrt{21}\x_1=frac{-b-sqrtDelta}{2a}=frac{3-sqrt{21}}{2}approx-0,79129\x_2=frac{-b+sqrtDelta}{2a}=frac{3+sqrt{21}}{2}approx3,79129 [/latex] c) (x+3)²-(4-x)(4+x)=2(x-1)²+1 x²+2·3·x+3²-(4²-x²)=2(x²-2·1·x+1²)+1 x²+6x+9-(16-x²)=2(x²-2x+1)+1 x²+6x+9-16+x²=2x²-4x+2+1 2x²+6x+-7=2x²-4x+3 6x+-7=-4x+3 4x+6x=3+7 10x=10 x=1

Dodaj swoją odpowiedź